(untitled) - Mathur, Aditya P. (Delhi, India, 2008)
Foundations of Software Testing is the premiere example-based text and reference for establishing sound engineering practices in test generation, selection, minimization and enhancement, for software projects ranging from the most simple to the highly complex, to those used by government agencies such as the FAA. Foundations of Software Testing also covers data-flow based adequacy and mutation-based adequacy, which are the most powerful of the available test adequacy criteria. It distills knowledge developed by hundreds of testing researchers and practitioners from all over the world and brings it to readers in an easy to understand form.
Keywords: Computer software,Computer software,Phần mềm máy tính,Phần mềm máy tính; Quality control,Testing,Nghiên cứu,Kiểm sóat chất lượng